A strategy for the rapid discovery and validation of active diterpenoids as quality markers in different habitats of Langdu using ultrahigh‐performance liquid chromatography–tandem mass spectrometry with multivariate statistical analysis. Issue 13 (14th April 2022) - Fang, Linlin; Zhang, Jianbin; Li, Fengqi; Zhang, Yingli; Zhang, Baojing; Huang, Shanshan; Deng, Sa; Zhang, Houli; Yu, Zhenlong; Gao, Bihu; Wang, Chao; Ma, Xiaochi
Abstract : Langdu, known as a traditional Chinese medicine, was identified as the roots of species of Euphorbia ebracteolata Hayata and Euphorbia fischeriana Steud, displaying anti‐tuberculosis activity. To clarify the potent quality markers of Langdu, this research first developed a fast and sensitive ultrahigh‐performance liquid chromatography–tandem mass spectrometry method for the quantification of 13 diterpenoids in Langdu. The developed method was further applied in the analyses of 12 authentic E. ebracteolata and E. fischeriana samples collected in northern and southeastern China. Then, the anti‐tuberculosis evaluation of 12 batches of Langdu samples was performed in vitro. Finally, partial least squares discrimination analysis was used in the discrimination of E. ebracteolata and E. fischeriana from different origins and processing methods. Jolkinolide A (1 ), jolkinolide E (3 ), yuexiandajisu D (6 ), and ebractenone A (11 ) were identified as key, potent diterpenoids for the quality control of E. ebracteolata Hayata and E. fischeriana Steud. The present study established a qualitative chemical analysis method for Langdu ( E. ebracteolata and E. fischeriana ) and suggested the key bioactive components that will improve qualitative control methodology for this important medicine.